Strategies of Middle School Students in Memorizing the Qur'an: Case Study in the Tahfidz Class of Junior High School Ma’arif 1 Ponorogo - Karim Abdillah; Safiruddin Al-baqi (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Al-Qur'an is a guideline for Muslims, so it is the duty of Muslims to understand, apply it in life and memorize it if they can. Memorizing Al-Qur’an with so many letters and verses seems difficult to do, especially for student in high school. This study aims to determine the strategies of students in memorizing the Qur'an, and to know the supporting factors and inhibiting factors for the implementation of the Qur'an memorization strategy for students. This study used qualitative research methods with a case study approach. The subjects of this study were 7 subjects consisted of 5 students of tahfidz program and 2 teachers. Data collection techniques used are observation, interviews, and documentation. Data is analyzed by reducing data, presenting data, and presenting conclusions. The results of the research show that the main strategy used by students to memorize the Qur'an is the strategy of not switching to the next verse before the memorized verse is completely memorized, while the strategy in maintaining memorization is muraja'ah 3 times a month. Other findings indicate the existence of supporting and inhibiting factors in the implementation of the strategy to memorize the Qur'an. Supporting factors consist of internal factors which include intention, willingness and determination, self motivation, and external factors which include teacher, friends, family, sanctions and existing facilities. While inhibiting factors consist of internal factors which include teacher saturation, student saturation, boredom, lack of interest in children, teacher delay, while external includes long verses, lack of time and family problems